KNOWLEDGE DISSEMINATION DALAM PELESTARIAN PENGETAHUAN LOKAL ADAIK SALINGKA NAGARI DI KURAI LIMO JORONG KOTA BUKITTINGGI - M Fadli (UIN Imam Bonjol Padang, 2021)
ABSTRACT The research is further investigated, to describe activities of knowledge dissemination of a pattern of exchange of indigenous knowledge Kurai Limo Jorong Bukittinggi city society. The methodology used and the qualitative method by approach case study. The data collection was done with the study of the field , interview, and study documentation. The results of the study showed knowledge dissemination in the preservation of the local knowledge in Bukittinggi city performed with the collaboration of the regional government, a local institution, and the community with local knowledge way disseminated in the form of explicit to society through: ( a ) customary workshop and a seminar, ( b ) festival, and ( c ) digital package information on various platforms. The involvement of regional administrations in the preservation of their area ( indigenous knowledge ), strategy is a movement in the preservation of the acceleration of local knowledge. The involvement of regional administrations in the preservation of their area (Indigenous knowledge), strategic is a movement in the preservation of the acceleration of indigenous knowledge. Key Words: knowledge dissemination, indigenous knowledge, preservation, Minangkabau ABSTRAK Penelitian ini merupakan penelitian lanjutan, yang mendeskripsikan kegiatan knowledge dissemination dari pola exchange of indigenous knowledge Adaik Salingka Nagari masyarakat Kurai Limo Jorong Kota Bukittinggi. Metode penelitian yang digunakan yaitu metode kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan dengan studi lapangan, wawancara, dan studi dokumentasi. Hasil penelitian menujukkan knowledge dissemination dalam pelestarian pengetahuan lokal Adaik Salingka Nagari di kota Bukittinggi dilakukan dengan kolaborasi antara pemerintah daerah, institusi lokal, dan masyarakat dengan cara mendiseminasikan pengetahuan lokal dalam bentuk eksplisit pada masyarakat luas : (a) lokakarya adat dan seminar, (b) festival, (c) paket informasi pada berbagai platform digital. Keterlibatan pemerintah daerah dalam pelestarian pengetahuan lokal (indigenous knowledge), merupakan sebuah langkah strategis dalam percepatan dalam preservasi pengetahuan lokal.